Clays and Clay Minerals, Vol. 57, No. 4, 476–485, 2009. - Lessovaia, S. N.; Polekhovsky, Yu. S. (My University, 2009)
The influence of epigenetic (pre-pedogenetic) alteration of basic and ultrabasic rocks leading to the formation of phyllosilicate mineral associations is not well known. The purpose of this study was to gain further understanding of the processes involved by investigating the mineral associations of shallow soils underlain by amphibolites and metamorphosed gabbro-diabases (East Fennoscandia) and by serpentinous dunites (olivinite) and metagabbro amphibolites (the Ural Mountains). Where phyllosilicates were absent from the bedrock, they were also absent from the sola. The pedogenic alteration of the initial mineral soil matrix was very weak and did not result in a significant accumulation of phyllosilicates in the soils (East Fennoscandia). Pedogenesis enhanced the transformation of phyllosilicates, a process initiated by epigenic rock alteration. Phyllosilicates in the sola from basic and ultrabasic rocks of the Polar Urals were largely inherited accordingto their origin. The inherited phyllosilicate association of the sola from ultrabasic rocks included talc, serpentine, and chlorite. Saponite resulted from pedogenesis; its distribution in various thin soils dependingon the processes of neoformation and decomposition, the latter probably taking place under the influence of lichens and moss. Chlorite and illite and products of their transformation, includingver miculite, comprise the phyllosilicate association of a solum from basic rock, and traces of talc were found. The distribution of vermiculite and randomly interstratified chlorite-vermiculite (C-V) depended on the processes of chlorite vermiculitization and vermiculite decomposition.
Mineralogical Composition Of Shallow Soils On Basic And Ultrabasic Rocks Of East Fennoscandia And Of The Ural Mountains, Russia
gsccm57408-les.pdf-- 1.11MB
Keywords: Periodicals; Geology; Basic and Ultrabasic Rocks; Mineral Transformation; Pedogenesis; X-ray Diffraction